Health Measures Incorporated by Kerala Government Against Covid-19 Outbreak - S, BLESSY PUSHPARATHNA; ANJALI, A.K.; NP, MURALIDHARAN (The journal of contemporary issues in business and government, 2020)
Coronavirus disease COVID-19 is an infectious disease, first discovered in China. This outbreak of 2019 novel virus disease in China spread quickly worldwide. In 2002 the humankind first witnessed SARS-COV, and COV was believed to be zoonotic. The source of origination and transmission are important to determine and understand the virus and to discover new preventive strategies. Coronavirus being a highly mutable virus made it difficult for the discovery of the vaccine. Most of the people infected experience mild to moderate respiratory illness. Other common symptoms include fever, cough, and myalgia or fatigue. Some patients may have a headache or hemoptysis and can be relatively asymptomatic. The best way to prevent and slow down transmission is to be aware of the COVID-19 virus, the disease it causes, and how it transmits. The government has taken various health measures against the COVID19 outbreak like practising respiratory etiquette, quarantining and social distancing, practising 1m apart, use of personal protective equipment, hand hygiene, water sanitation, and hygiene, waste management, surface infection, hospital and home isolation, mental health management, immunization and ban on smoking and travel restrictions. The government thus implemented these measures and it is the role of every citizen to follow these measures and pave the way for a better living.